Re-Engineering Library and Information Services: A Case Study of NSDRC/IMU Library - Padmashree, S.; Sasikala, C. (Journal of Information and Knowledge, 2017)
This paper presents a report on the transition from old system to new and improving the library collection, services and ambience by adopting new technologies and converting the library to a modern information centre with the objective of putting the end users in contact with the information needed by them, whether it is on paper or stored digitally.